A Note on the Impact on Sales from Introducing Healthy Labeled Meals on the Lunch Menu - Linda Thunström; Jonas Nordström (Lund University, School of Economics and Management, Department of Economics, 2012)
Menu labeling of prepared meals away from home is a policy designed to help consumers make healthier food choices. In this paper, we use a field experiment to analyze if a restaurant benefits from introducing a healthy labeled meal on its menu by experiencing an overall increase in sales. We cannot reject the hypothesis that sales are the same before and after the introduction of a healthy labeled meal on the menu, i.e., our data does not support the idea that restaurants increase their sales from supplying a healthy labeled meal.
Keywords: D22; D83; 330; healthy labeled meals; sales; field experiment